Penerapan Metode Activity Based Costing dalam Penentuan Harga Pokok Jasa Layanan Transaksi Mobile Banking Sinar SIP pada PT. Bank Sinar Harapan Bali Kantor Pusat Operasional - treanika, dewa ayu putu (E-Jurnal Akuntansi, 2012)
ABSTRACT This research is to identify and obtain information on the calculation and comparison of the cost of transaction services Sinar Sip using traditional cost accounting calculations with ABC, using secondary data from company financial statements. Based on the calculation and comparison in mind, that the comparison of the cost of transaction services Sinar Sip by traditional methods with the ABC method. Apparently there is a material difference. There is a difference in cost is lower than the Bank's management setting rays with the results of calculations using the ABC approach. That is the difference between the base price of 262.799 for cash deposit, cash withdrawal Rp. 377.699, bill payment of Rp. 358.499, Axis air time top up to Rp. 326.599 and the transfer of Rp. 164.94. Keyword:  Activity Based Costing, Harga Pokok, Mobile Banking